About Face: How the People’s Republic of China Harnessed Health to Leverage Soft Power on the World Stage - Kadetz, Paul; Stanley-Baker, Michael (Frontiers in Human Dynamics, 2022)
In the fifteen year period from 1964-1979, The People's Republic of China engaged in an unprecedented number of domestic and international health campaigns that were utilized for China's entrance onto the world stage. From Mao Zedong's vision of a new form of medicine via the unification of Chinese medicines and biomedicine to the adoption of a Chinese model of health care integration and primary health care by the World Health Organization in the Declaration of Alma Ata, the PRC entered the world stage through its 'health exports' and its distinctive adaptation of modernity to serve domestic, and often foreign policy goals. These exports include Sino-African health diplomacy; the globalization of Traditional Chinese Medicine, and in particular the global utilization and scientific recognition of the antimalarial artemisinin derived from the Chinese herb Qinghao; and a model of primary and rural universal health care utilizing community health workers that garnered multilateral support. However, the face of benevolence displayed on the world stage was often contradicted by what was occurring domestically, behind the scenes, with the marked state enforcement of many of these same health campaigns in front of the backdrop of the cultural revolution. This paper examines if, and how, the West may have orientalized and romanticized China's health care exports. Furthermore, we analyze the World Health Organization's adoption and global promotion of a model for universal health care that was only able to be achieved via the often brutal enforcement of the state, whilst rejecting grass-roots movements enacted during the same period, such as the practitioner-led integration of Ayurvedic medicine in India.